2006
DOI: 10.1002/rcm.2361
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring enzyme‐catalyzed production of glucosamine‐6P by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry: a new enzymatic assay for glucosamine‐6P synthase

Abstract: A matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOFMS) method for quantification of D-glucosamine-6P (GlcN-6P) that allows the kinetic study of glucosamine-6P synthase (Glms) is presented. The present report describes the optimization of the different steps of a new enzymatic assay for Glms based on in situ N-acetylation of GlcN-6P and MALDI-TOFMS analysis using N-(13C2)acetylglucosamine-6P as internal standard. Since no isotopically substituted GlcN-6P was available, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Earlier studies have shown that MALDI-tof-MS can be used for quantitative purposes, for example, it was used for the determination of substrates and products of an immobilized lipase-catalyzed reaction in non-buffered organic solvent. 11 Similarly, the conversion of D-fructose into glucosamine-6P catalyzed by glucosamine-6P synthase was analyzed by MALDI-MS. 12 In our previous studies, we have used MALDItof-MS for the quantification of cystatin, 13 as well as to quantify the inhibition of glycation of low abundant proteins by albumin. 14 In this study, we describe a high-throughput MALDI-tof-MS-based in vitro insulin glycation assay for screening glycation inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that MALDI-tof-MS can be used for quantitative purposes, for example, it was used for the determination of substrates and products of an immobilized lipase-catalyzed reaction in non-buffered organic solvent. 11 Similarly, the conversion of D-fructose into glucosamine-6P catalyzed by glucosamine-6P synthase was analyzed by MALDI-MS. 12 In our previous studies, we have used MALDItof-MS for the quantification of cystatin, 13 as well as to quantify the inhibition of glycation of low abundant proteins by albumin. 14 In this study, we describe a high-throughput MALDI-tof-MS-based in vitro insulin glycation assay for screening glycation inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions occurred in a non‐disturbing diluted Tris buffer and the N ‐acetylation was necessary to better distinguish glucosamine phosphate from fructose phosphate of a similar mass. For measuring acetylated glucosamine phosphate alone, the authors used a THAP matrix (Maillard et al, 2006) whereas 9‐aminoacridine allowed to measure N ‐acetylated glutamate and N ‐acetylglucosamine‐6‐phosphate simultaneously in the negative mode (Gaucher‐Wieczorek et al, 2014). The determined kinetic constants K m and k cat for the two substrates were comparable with data from other methods.…”
Section: Maldi‐based Assays Of Other Enzymesmentioning
confidence: 99%
“…Using this approach, they achieved good linear relationships and produced kinetic values in line with those reported from other methods. Similarly, Maillard et al (2006) developed a MALDI‐TOF‐based assay to evaluate the kinetic parameters of glucosamine‐6P synthase. They validated the method by determining the Km for fructose‐6P and with a known competitive inhibitor.…”
Section: Mass Spectrometry For Enzyme Assaysmentioning
confidence: 99%